A protocol for flow cytometric determination of expected chromosome number of Brassica juncea L. introgression lines - Chhaya Atri; S.S. Banga (Journal of Oilseed Brassica, 2026)
Flow cytometry was used to estimate the amount of DNA in nuclei of a set of Brassica juncea introgression linescarrying genomic segments from B. fruticulosa. Solanum lycopersicum L. cv. ‘Stupicke´ with 2C nuclearDNA content of 1.96 pg was used as an internal reference standard. The 2C DNA content of 2.440 pg wasworked out for the standard, B. juncea cv. RLC- 1. The 2C DNA content of B. juncea introgression linesranged between of 2.248 pg (AD4K2-196) and 2.538 (AD3L-526, AD3L-459). Increase in the genome sizeas compared to the standard B. juncea parent, RLC 1 may indicate the addition of alien chromatin from B.juncea. A reduction in genome size may indicate the chromatin loss. Results indicated a high correlation(0.84) between the relative nuclear DNA content and the expected chromosome number. The studies showedthat flow cytometry can be effectively used to gain more insight into the variation and transmission of DNAcontent within the alien introgressed populations of crop Brassica species.